Differentiating Instruction whit Technology in Middle School Classrooms/Grace E. Smith - Smith .Grace E (State of America :iste, 2009)
Trata del differentiating Instruction whit Technology in Middle School Classrooms.
1.Technologus Big picture 2.Differentiated Instruction and middle 3.Using the new web
incluye ìndice
Col. Educ
Keywords: 1.TECHNOLOGY AND LEARNING 2.THE LEARNING ENVIRONMENT 3.THE ESSENTIAL NINE